Ответы и объяснения

2012-12-20T02:52:12+04:00

1) Решил в личке

2) 5sin²x-14sinxcosx-3cos²x=2 

 5sin²x-14sinxcosx-3cos²x=2sin²x+2cos²x

 3sin²x-14sinxcosx-5cos²x=0 | ÷cos²x

3tg²x-14tgx-5=0

Замена tgx=t

3t²-14t-5=0

D=196+60=256=16²

t=(14-16)/6=-1/3

t=5

x = -arctg (-1/3) + IIn, n3 Z

x = arctg 5 + IIk, k 3 Z

3) sin⁶x+sin⁴xcos²x=sin³xcos³x+sinxcos⁵x=

sin⁴x(sin²x+cos²x)= sinxcos³x(sin²x+cos²x) 

sin⁴x-sinxcos³x=

sinx(sin³x-cos³x) 

sinx(1-cos³x-cos³x)=sinx(1-2cos³x)=

-sinx(2cos³x-1) 

-sinxcos2x